Functional characteristics and therapeutic potential of SLC41 transporters - Takayuki Nemoto; Hideaki Tagashira; Tomo Kita; Satomi Kita; Takahiro Iwamoto (Elsevier, 2023)
Magnesium (Mg2+) plays an important role in various cellular functions such as protein synthesis, DNA stability, energy metabolism, enzyme and channel activities, and muscle contractility. Therefore, intracellular Mg2+ concentration is tightly regulated by multiple Mg2+ transporters and channels. So far, various candidate genes of Mg2+ transporters have been identified, and the research on their structure and function is currently in progress. The Solute Carrier 41 (SLC41) family, which is related to the bacterial Mg2+ transporter/channel MgtE, comprises three isoforms of SLC41A1, SLC41A2, and SLC41A3. Based on recent studies, SLC41A1 is thought to mediate Mg2+ influx or Na+-dependent Mg2+ efflux across the plasma membrane, whereas SLC41A2 and SLC41A3 may mediate Mg2+ fluxes across either the plasma membrane or organellar membranes. Intriguingly, SLC41A1 variants have been identified in patients with Parkinson's disease (PD) and nephronophthisis-related ciliopathies. Further genetic analyses reveal the association of SLC41A1 polymorphisms with PD risks. This review highlights the recent advances in the understanding of the molecular and functional characteristics of SLC41 family towards its therapeutic and diagnostic applications.